Development of Canva-Based Learning Media for Pancasila Education in Grade XI Social Sciences at MA Al Fattahiyyah - Rohma Nugraheni; Nurna Listya Purnamasari (Darul Yasin Al Sys, 2026)
Pancasila Education learning at MA Al Fattahiyyah has predominantly relied on worksheets and lecture-based instruction, resulting in limited student engagement, reduced learning motivation, and difficulties in understanding instructional content. This condition highlights the need for innovative digital learning media that align with the characteristics of contemporary learners. This study aimed to develop Canva-based learning media for the topic “Citizens’ Attitudes toward the Implementation of the Governmental System of the Republic of Indonesia” in Pancasila Education and to examine the validity of the developed product. A Research and Development (R&D) approach was employed using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants included media experts, content experts, and Grade XI Social Sciences students at MA Al Fattahiyyah. Data were collected through observation, interviews, questionnaires, and documentation and were analyzed using quantitative and qualitative descriptive techniques. The findings reveal that the developed Canva-based learning media obtained a media expert validation score of 94%, categorized as highly valid, and a material expert validation score of 93%, also categorized as highly valid. The small-group trial produced a score of 77%, categorized as valid, while the large-group trial achieved 83%, categorized as highly valid. Overall, the product obtained an average feasibility score of 86.75%, indicating a highly valid level of quality and suitability for instructional use. The study concludes that Canva-based learning media are feasible as an alternative instructional resource for Pancasila Education. These findings contribute to the development of digital learning media by demonstrating the relevance of interactive, visually supported instructional resources in improving learning quality, supporting the implementation of the Merdeka Curriculum, and creating more engaging and meaningful learning experiences for students.